Transplante autólogo de células-tronco de medula óssea em pacientes com trauma raquimedular - Mendonça, Marcus Vinícius Pinheiro (2014)
Despite the advancement in the care of patients with spinal cord injury, currently there is no specific treatment for neurological lesion. Therapy with mesenchymal stem cells from bone marrow (BMMC) has shown to be a safe and promising technique in various medical fields. The objective of this study is to evaluate the safety of autologous BMMC transplantation for the treatment of chronic spinal cord injury of traumatic origin.Fourteen paraplegic patients (classified as A in ASIA scale) with at least 6-month thoracic or thoracolumbar spinal cord injurywere selected. They underwent aspiration of bone marrow tissue from the iliac crest with further expansion and in vitro characterization; by means of microsurgical procedure, the BMMC suspension was introduced at the level of the spinal cord injury. A 6-month clinical follow-up was performed after surgery, including functional and imaging tests. There was a change in ASIA scale in 7 patients, increased bladder capacity in 5 patients and appearance of the SSEP waveform in one patient. Throughout the observation period, no major complications were observed. The present protocol proved to be safe and, due to significant improvements in neurological symptoms in many patients, also a potentially promising therapeutic method for patients with spinal cord injury.